Preparation of paddy straw based complete feed pellets and their impact on the performance of buffalo calves - WADHWA, M; HUNDAL, J S; BAKSHI, M P S (The Indian Journal of Animal Sciences, 2021)
This study was planned to prepare paddy straw based complete feed pellets and to assess their impact on the performance of buffalo calves. Iso-nitrogenous and isocaloric complete feed pellets containing 25, 35 and 45% paddy straw, alfalfa hay and concentrate mixtures were prepared. The roughage to concentrate ratio in the pellets was maintained at 65:35. The CP, EE and cell wall contents in all pellets were comparable. The bulk density of complete feed pellets increased (p